2009
DOI: 10.1007/s10495-008-0295-5
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenite induces apoptosis by ROS-mediated endoplasmic reticulum stress and mitochondrial dysfunction in human acute promyelocytic leukemia NB4 cells

Abstract: Sodium selenite-induced reactive oxygen species generation is an early event that triggers endoplasmic reticulum stress mitochondrial apoptotic pathways in NB4 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 34 publications
5
67
0
2
Order By: Relevance
“…Moreover, activated Akt also stimulates the mTOR/P70S6-kinase pathway, whose activation is required for the initiation of protein synthesis (14,15). Our former studies showed that the expression of p-Akt, down-stream factor of PI3K, decreased in selenite induced apoptosis in NB4 cells (16). Consequently, we postulated that the PI3K pathway plays an important role in the inhibition of autophagy and the increase of apoptosis in NB4 cells.…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, activated Akt also stimulates the mTOR/P70S6-kinase pathway, whose activation is required for the initiation of protein synthesis (14,15). Our former studies showed that the expression of p-Akt, down-stream factor of PI3K, decreased in selenite induced apoptosis in NB4 cells (16). Consequently, we postulated that the PI3K pathway plays an important role in the inhibition of autophagy and the increase of apoptosis in NB4 cells.…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies indicated that the antitumor activity of selenium compounds was often attributed to drug-induced apoptosis (5,6,20). Here we addressed that autophagy acted as another essential mechanism for the application of selenite in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences confirmed the application of selenite in studies of cell proliferation and cancer (3,4). Previous results suggested supranutritional doses of selenite promoted cell death through mitochondria-or ER stress-mediated apoptotic pathway in human leukemia cell lines (5,6). Furthermore, autophagy has recently been considered as an alternative mechanism of cell death induced by selenite, which caused concurrence of autophagy and apoptosis in leukemia cells (7,8).…”
Section: Introductionmentioning
confidence: 87%
“…cells by the generation of reactive oxygen species (ROS) [24]. In addition, many organic/inorganic selenium compounds have been found capable of inducing apoptotic death of tumour cells [25,26].…”
Section: Introductionmentioning
confidence: 99%